Requirements for human haematopoietic stem/progenitor cells. Issue 4 (22nd December 2021) - Nan, Xue; Zhang, Bowen; Hao, Jie; Yue, Wen; Fu, Boqiang; Qu, Mingyi; Zhang, Yu; Wang, Haiyang; Fang, Fang; Wei, Jun; Li, Qiyuan; Hu, Shijun; et al.
Abstract: 'Requirements for human haematopoietic stem/progenitor cells' is the first set of guidelines on human haematopoietic stem/progenitor cells in China, jointly drafted and agreed upon by experts from the Chinese Society for Stem Cell Research. This standard specifies the technical requirements, inspection methods, inspection rules, instructions for usage, labelling requirements, packaging requirements, storage requirements and transportation requirements for human haematopoietic stem/progenitor cells, which is applicable to the quality control for human haematopoietic stem/progenitor cells. We hope that publication of these guidelines will promote institutional establishment, acceptance and execution of proper protocols, and accelerate the international standardization of human haematopoietic stem/progenitor cells for applications.